Mechanism of action of 5-arninosalicylic acid - N. A. Punchard; S. M. Greenfield; R. P. H. Thompson (Mediators of Inflammation)
5-Aminosalicylic Acid (5-ASA) has been used for over 50 years in the treatment of inflammatory bowel disease in the pro-drug form sulphasalazine (SASP). SASP is also used to treat rheumatoid arthritis. However whether the therapeutic properties of SASP are due to the intact molecule, the 5-ASA or sulphapyridine components is unknown. Several mechanisms of action have been proposed for 5-ASA and SASP including interference in the metabolism of arachidonic acid to prostaglandins and leukotrienes, scavenging,of reactive oxygen species, effects on leucocyte function and production of cytokines. However, it is unlikely that the anti-inflammatory properties of SASP and 5-ASA are due to several different properties but more likely that a single property of 5-ASA explains the theraapeutic effects of 5-ASA and SASP. Reactive oxygen species (ROS) are involved in the metabolism of prostaglandins and leukotrienes and can act as second messengers, and so the scavenging of ROS may be the single mechanism of action of 5-ASA that gives rise to its antiinflammatory effects in both inflammatory bowel disease and rheumatoid arthritis.